2001
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path725>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemotactic protein-1, -2, and -3 are distinctively expressed in portal tracts and granulomata in primary biliary cirrhosis: implications for pathogenesis

Abstract: The monocyte chemotactic proteins (MCPs) form a distinct structurally related subclass of C±C chemokines. MCPs select speci®c target cells due to binding to a distinct set of chemokine receptors and because of their effects on monocytes, and may participate in the process of granuloma formation during bacterial and/or mycobacterial infections. The aetiology of primary biliary cirrhosis (PBC) is still unclear, although bacterial infection and autoimmune processes have been implicated. In this study, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 30 publications
2
53
0
1
Order By: Relevance
“…26,27 The finding of MCP-1 expression in hepatocytes, particularly those at the edge of active fibrosis, is novel and may be unique to cholestatic liver diseases such as BA and CFLD, because previous studies in adult chronic viral hepatitis have reported expression of MCP-1 limited to inflammatory cells, cholangiocytes, and HSCs. Chemokines generally regulate leukocyte recruitment to various tissues of the body, including the liver.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The finding of MCP-1 expression in hepatocytes, particularly those at the edge of active fibrosis, is novel and may be unique to cholestatic liver diseases such as BA and CFLD, because previous studies in adult chronic viral hepatitis have reported expression of MCP-1 limited to inflammatory cells, cholangiocytes, and HSCs. Chemokines generally regulate leukocyte recruitment to various tissues of the body, including the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Cameron et al reported persistent activation of macrophages in livers of patients with primary sclerosing cholangitis, which participate in the chronic release of TGF-γ and contribute to the chronic inflammation and fibrosis [27]. Primary biliary cirrhosis is associated with Kupffer cell portal tract infiltrates that express monocyte chemotactic proteins, resulting in persistent recruitment of monocytes surrounding bile ducts [28].…”
Section: Discussionmentioning
confidence: 99%
“…8 Biliary epithelial cells (BECs) are known as immunologically potent cells, and BECs of inflamed bile ducts actively participate in inflammation by secreting cytokines and expressing immune receptors. 9,10 Chemokines also are expressed on pathological bile ducts. 10,11 For ex-ample, Terada et al 12 reported that stromal-derived factor 1 expressed on bile ducts is responsible for the migration and recruitment of lymphoid cells in portal tracts and around bile ducts in primary biliary cirrhosis (PBC) as well as in chronic viral hepatitis (CVH).…”
mentioning
confidence: 99%
“…9,10 Chemokines also are expressed on pathological bile ducts. 10,11 For ex-ample, Terada et al 12 reported that stromal-derived factor 1 expressed on bile ducts is responsible for the migration and recruitment of lymphoid cells in portal tracts and around bile ducts in primary biliary cirrhosis (PBC) as well as in chronic viral hepatitis (CVH). Although the upregulation of fractalkine and CX3CR1 expression has been reported in hepatic parenchyma and bile ductules of hepatitis C virus-infected livers, 13 their expression and immunopathological significance remain unexplored in normal and pathological bile ducts.…”
mentioning
confidence: 99%